PEMANFAATAN TEKNOLOGI INFORMASI UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN - Muthmainnah Muthmainnah; Fajriana Fajriana; Deassy Siska (Teknik Informatika Universitas Malikussaleh, 2017)
E-Learning is an educational system that utilizes electronic and applications to support the development of teaching and learning activities typically using internet media, intranet or other computer network media. Teaching and learning process in SMA Negeri 3 Lhokseumawe and SMK Swasta Ulumuddin Lhokseumawe is still conducted directly through face to face.E-Learning helps the learning process becomes more effective and efficient. The learning activity begins with the introduction to internet and website.Then the students are taught about how to use e-learning in teaching and learning process. E-Learning facilitates the teaching and learning process without being bound by time and place.The conclusion is E-Learning support teaching learning process in term of the communication of teachers and students, the material distribution, and the tasks distribution and collection.